Menerapkan Manajemen Pelayanan Berbasis SOP di Gereja - Maria Wijiati (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2020)
When viewed at the present time, church service management based on SOP (Standard Operating Procedures) in providing quality of service is less considered. This can be seen by the dependence of subordinates / workers / staff to the leader in running the service so that errors often occur in it and as a result can not provide good quality of service to the congregation, the services provided by the church are not in accordance with the expectations of the congregation. Management of church services is a very important process in serving the congregation. Every minister in all areas of service in a church should have a standard operating procedure that has been determined. Such as the attitude of serving the congregation, appearance when serving the congregation, knowledge and skills in serving the congregation according to their respective fields of service. The purpose of this paper is to determine the quality of services that exist in the church, to know the extent of service management based on SOP (Standard Operating Procedures) in the church and to determine the standardization of service management in the church. Based on the results of this paper, we get the fact that by implementing service management based on SOP (Standard Operating Procedures) in the church, the congregation can be served well and effectively so as to produce satisfaction for the congregation. Abstrak Jika dilihat pada masa sekarang ini, manajemen pelayanan gereja yang berbasis SOP (Standar Operasional Prosedur) dalam memberikan kualitas pelayanan kurang diperhatikan. Hal ini dapat dilihat dengan adanya ketergantungan bawahan/ pengerja/ staff kepada pemimpin dalam menjalankan pelayanan tersebut sehingga seringkali terjadi kesalahan di dalamnya dan akibatnya tidak dapat memberikan kualitas pelayanan yang baik kepada jemaat, pelayanan yang diberikan oleh gereja tidak sesuai dengan harapan jemaat. Manajemen pelayanan gereja ini merupakan proses yang sangat penting dalam melayani jemaat. Setiap pelayan dalam semua bidang pelayanan di gereja seharusnya mempunyai standar operasional prosedur yang sudah ditentukan. Seperti sikap melayani jemaat, penampilan saat melayani jemaat, pengetahuan dan keterampilan dalam melayani jemaat sesuai bidang pelayanan masing-masing. Tujuan tulisan ini adalah untuk mengetahui mutu pelayanan yang ada pada gereja, mengetahui sejauh mana manajemen pelayanan berbasis SOP pada gereja dan untuk mengetahui standarisasi manajemen pelayanan yang ada pada gereja. Berdasarkan hasil penulisan ini, memperoleh fakta bahwa dengan diterapkannya manajemen pelayanan berbasis SOP di gereja, maka jemaat dapat terlayani dengan baik dan efektif sehingga menghasilkan kepuasan bagi jemaat.